2001
DOI: 10.1074/jbc.m102457200
|View full text |Cite
|
Sign up to set email alerts
|

A Role of the C-terminal Part of p44 in the Promoter Escape Activity of Transcription Factor IIH

Abstract: The p44 subunit plays a crucial role in the overall activity of the transcription/DNA repair factor TFIIH: on the one hand its N-terminal domain interacts with and regulates the XPD helicase (1, 2); on the other hand, as shown in the present study, it participates with the promoter escape reaction. Mutagenesis along with recombinant technology using the baculovirus/insect cells expression system allowed us to define the function of the two structural motifs of the C-terminal moiety of p44: mutations within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
19
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
6
19
0
Order By: Relevance
“…9). These observations strongly suggest that p44 is involved in the transition stage, which confirms observations made previously (46,53). The bHLH and bHL regions of hTFIIE␤ may play distinct roles before and at transcription initiation.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…9). These observations strongly suggest that p44 is involved in the transition stage, which confirms observations made previously (46,53). The bHLH and bHL regions of hTFIIE␤ may play distinct roles before and at transcription initiation.…”
Section: Discussionsupporting
confidence: 78%
“…These observations support the notion that, once transcription is initiated at the initiation site of supercoiled templates, no additional requirements are needed to complete transcription, probably because the torsional stress from negative supercoiling is converted into the energy needed to open up the dsDNA, thereby allowing Pol II transcription to proceed (9,39). In contrast, extension of initiated transcripts through the transcription transition stage (promoter escape) might require TFIIH helicase activity when linearized templates are used (3,6,17,53). Thus, our observations as well as the data presented by Tremeau-Bravard and colleagues showing p44 involvement in the transcription transition stage (promoter escape) (53) clearly indicate that transcription with a supercoiled template reflects transcription initiation activity while transcription with a linearized template reflects the ability to transit from transcription initiation to elongation.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Prediction algorithms of miRNA target sites (miRGator) confirmed that these seven TFIIH-coding mRNAs are potentially targeted by miRNAs (Table S1). Because the p44 subunit plays a role in RNA pol II promoter-escape modulating transcription (27) and its coding mRNA presents only three predicted miRNA binding sites (miR-27a, miR-27b, miR-189), we focused our study on p44 mRNA. To experimentally identify miRNAs regulating p44 mRNA translation/stability, we used a method that allows the identification of miRNAs binding to a particular 3′ UTR in vivo (28) and further validated the interaction by intracellular localization/interaction with the RISC complex.…”
Section: Tfiih-coding Mrnas Are Regulated At the Posttranscriptional mentioning
confidence: 99%